Differential effects of wheat bran antioxidants on the growth dynamics of human cancer cells - Rahman, Md Sharifur (My University, 2025)
Wheat bran, rich in phenolic compounds like ferulic acid, possesses notable antioxidant properties that may contribute to cancer treatment strategies. This study examined the effects of hydrolyzed arabinoxylan oligomers (HAO) linked with ferulic acid from hard wheat bran on three human cancer cell lines: colon cancer (SW480), liver cancer (HepG2), and cervical cancer (HeLa). Cells were cultured in a three-dimensional (3D) PGmatrix and exposed to varying concentrations (100, 500, and 1000 [mu]g/ml) of wheat bran extracts (WBE). Results showed that WBE inhibited growth of SW480 cells, significantly reducing spheroid expansion and promoting dehydration. In contrast, HepG2 cells exhibited increased growth under WBE treatment, suggesting a non-toxic, growth-enhancing effect. No significant changes were observed in HeLa cell growth, with cell viability remaining high across all treatments. These findings highlight the selective influence of WBE on cancer cell behavior, underscoring its potential for targeted, personalized cancer therapies. This study provides valuable insights into the application of antioxidant-rich compounds for modulating specific cancer cell dynamics, paving the way for novel therapeutic approaches.
Keywords: Wheat bran antioxidants; Hydrolyzed arabinoxylan oligomers; Cancer cell growth; 3D culture; Targeted cancer therapy